The construction of the local and the limits of contemporary community building in the United States - Fraser, James C. et al. (2003)
With new relationships between state and civil society, community building has arisen as a preferred mechanism to ameliorate urban poverty. Community building is a much-supported but under criticized paradigm, especially with respect to questions about the benefits that impoverished neighborhood residents actually acquire from these initiatives. The authors examine community building as a process that is related to larger agendas meant to enact certain productions of urban space and challenge many taken-for-granted notions about the realized benefits of this form of antipoverty work. Moreover, they argue that community-building initiatives occur in an increasingly globalized context, providing opportunities fo r stakeholders other than residents to promote certain productions of space and place. A case study is presented of an initiative occurring in a southern city in the United States to highlight the theoretical framework presented. - Reproduced.
Keywords: Community centres